CONSTRUCTION AND CALIBRATION OF THERMAL TRANSDUCERS FOR THE MEASUREMENT OF WATER CONTENT OF SOILS - da Silva, Jonas Cegelka; Borges, Pedro Augusto Pereira; de Oliveira, Fabiane Avena (Scientia Plena, 2011)
The knowledge of the soil characteristics and properties are fundamental for agriculture and engineering. The present water in the soil influences those properties strongly and for that, the accurate, fast and of low cost measurement of the water content is a necessity in projects of scientific research, irrigation, constructions of dams and highways. The working principle of the thermal transdutor to measure the water content, proposed in this work, is the variation of the thermal diffusivity in function of the soil water content. The diffusivity was estimated through the heat transfer inverse problem. The direct problem was modeled using the energy equation in cylindrical coordinates, with first kind boundary conditions, determined experimentally. The inverse problem was solved by the Search in Net Modified Method .Calibration curves were built with the diffusivity data in function of the water content, using no lineal adjusts of a sigmoid function, for each soil type. The precision of the transdutor was analyzed calculating the standard deviation of the diffusivity measures. The mistake of a double standard deviation in diffusivity estimation results in a mistake smaller than 10% in the calculation of the water content. The thermal transducers can be used in situations where they are installed in the same position for all measures, such as in the irrigation by aspersion or by dripping and laboratory experiments.